2017
DOI: 10.1177/0333102417723570
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in children presenting migraine with aura: Association of hypoperfusion detected by arterial spin labelling and vasospasm on MR angiography findings

Abstract: Objective A child presenting with a first attack of migraine with aura usually undergoes magnetic resonance imaging (MRI) to rule out stroke. The purpose of this study was to report vascular and brain perfusion findings in children suffering from migraine with aura on time-of-flight MR angiography (TOF-MRA) and MR perfusion imaging using arterial spin labelling (ASL). Methods We retrospectively included all children who had undergone an emergency MRI examination with ASL and TOF-MRA sequences for acute neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…69 Using ASL and MR angiography in retrospective chart analysis, it was found that in pediatric patients with MA, there was homolateral hypoperfusion of the side of vasospasm. 70 A more recent study also using ASL found differences between pediatric migraine patients with and without perfusion changes during migraine. This study has found that patients who had perfusion abnormalities were more likely to have aura, motor disabilities, confusion, and hospitalization.…”
Section: Perfusionmentioning
confidence: 95%
“…69 Using ASL and MR angiography in retrospective chart analysis, it was found that in pediatric patients with MA, there was homolateral hypoperfusion of the side of vasospasm. 70 A more recent study also using ASL found differences between pediatric migraine patients with and without perfusion changes during migraine. This study has found that patients who had perfusion abnormalities were more likely to have aura, motor disabilities, confusion, and hospitalization.…”
Section: Perfusionmentioning
confidence: 95%
“…These findings implicate pericytes as key players in pain that arises from altered CBF, for example in migraine and chronic pain conditions associated with altered blood vessel function 63 . Blood oxygen level-dependent technology has linked generalised cerebral hypoperfusion with severe pain in migraineurs, which was associated with concurrent vasospasm 64 . Induced hypoxia worsened pain in response to stimuli designed to invoke an episode.…”
Section: Pericytes In Haemodynamic Regulationmentioning
confidence: 99%
“…Recently, ASL is an emerging MRI sequence that can be easily performed without contrast injection or any side effects. Some recent studies stressed the significant abnormalities in somatosensory cortex or other brain regions of migraineurs [ 51 , 52 ], while one study declared that they didn’t see and significant changes [ 53 ]. We hope that the impact of the susceptibility of estrogen drop on brain activity could also be reflected in functional imaging.…”
Section: Discussionmentioning
confidence: 99%